Two Dimensional Labelled Security Model with Partially Trusted Subjects and Its Enforcement Using SELinux DTE Mechanism - Janáček, Jaroslav (Networked Digital Technologies, 2010)
Personal computers are often used in small office and home environment for a wide range of purposes – from general web browsing and e-mail processing to processing data that are sensitive regarding their confidentiality and/or integrity. Discretionary access control mechanism implemented in the common general purpose operating systems is insufficient to protect the confidentiality and/or the integrity of data against malicious or misbehaving applications running on behalf of a user authorized to access the data. We present a security model, based on the Bell-La Padula and Biba models, that provides for both confidentiality and integrity protection, and that uses a notion of partially trusted subjects to limit the level of trust to be given to the processes that need to to pass information in the normally forbidden direction. We discuss a way to enforce the model’s policy using SELinux mechanism present in current Linux kernels.